Before I Die: death positivity and the community nursing contribution. (2nd December 2021) - Murphy, Sam
Abstract : This article explores the contextual backdrop of the death-positive movement that inspired the discussion group Before I Die: Worcestershire, along with the motivations behind its creation. It explores the balance between practical, planning discussions and open-ended talks held by the group, emphasising the importance of creativity when responding to the topics of death and dying. The collaborative efforts between Before I Die: Worcestershire and other groups and persons involved in the death-positive movement are also highlighted. This article considers the potential of grassroots community movements to engage people to make plans for their dying, regardless of circumstances and background. It argues that death-positive movements, projects and initiatives can be a valuable way for community nurses to engage with the population they serve.